Extracellular vesicles participate in the pathogenesis of sepsis - Tian, Chang; Wang, Ke; Zhao, Min; Cong, Shan; Di, Xin; Li, Ranwei (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is one of the leading causes of mortality worldwide and is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. The early diagnosis and effective treatment of sepsis still face challenges due to its rapid progression, dynamic changes, and strong heterogeneity among different individuals. To develop novel strategies to control sepsis, a better understanding of the complex mechanisms of sepsis is vital. Extracellular vesicles (EVs) are membrane vesicles released from cells through different mechanisms. In the disease state, the number of EVs produced by activated or apoptotic cells and the cargoes they carry were altered. They regulated the function of local or distant host cells in autocrine or paracrine ways. Current studies have found that EVs are involved in the occurrence and development of sepsis through multiple pathways. In this review, we focus on changes in the cargoes of EVs in sepsis, the regulatory roles of EVs derived from host cells and bacteria, and how EVs are involved in multiple pathological processes and organ dysfunction in sepsis. Overall, EVs have great application prospects in sepsis, such as early diagnosis of sepsis, dynamic monitoring of disease, precise therapeutic targets, and prevention of sepsis as a vaccine platform.